AN EXCIMER LASER-BASED MICRO ANALYTICAL PREPARATION TECHNIQUE FOR IN-SITU OXYGEN ISOTOPE ANALYSIS OF SILICATE AND OXIDE MINERALS - Wiechert U.; Hoefs J. (My University, 1995)
A new excimer laser system for in-situ analysis of oxygen isotope ratios of silicates and oxides is described. In contrast to IR lasers the UV laser does not cause any fractionation during laser ablation due to edge or other effects. Analytical reproducibility and precision is equivalent to the conventional method for sample sizes of 0.1 mg, which is the minimum amount required by our mass-spectrometer system. Refractive minerals like olivine and garnet can be analyzed with a precision comparable with conventional analyses of highly reactive minerals, quartz, however, which is transparent at 248 nm does cause problems. Other advantages and disadvantages of our UV laser system are discussed.